Retroperitoneal Liposarcomas: A Representative Literature Review Occasioned by a Rare Case of Laterelapse Abdominal Liposarcoma. Issue 2 (April 2016) - Pisani, Michela; Al-Buheissi, Salah; Whittlestone, Tim
Soft tissue sarcomas (STS) are rare and heterogeneous tumours representing approximately 0.7%-1% of all adult tumours. In the adults and among the retroperitoneal sarcomas (RPS), Liposarcoma (LS) is the most common variant accounting for 12% −20% of all sarcomas and up to 45% of sarcomas at retroperitoneal localization. A rare case of LS relapsed after 15 years is giving the occasion to review the published literature and emphasise the followings concepts: 1) Despite extensive surgery remains the mainstay of treatment for localized STS at present, anatomical complexity and occult localization result in local recurrence in the majority of patients; 2) The role of imaging and tumour markers is still limited; 3) Indefinite prolonged surveillance is a key point of treatment; 4) Referral to tertiary centres with dedicated Retroperitonal Surgeons and Oncology expertise is mandatory.